A kind of diclofenac sodium sustained-release tablet and preparation method thereof
Through the combined coating of modified colloidal silica and povidone K30 and the secondary coating technology of nano-silica activation coating liquid, the tendency and adverse reactions of diclofenac sodium sustained-release tablets in the gastrointestinal tract are solved. Frequent problems have achieved stable sustained release effect and high bioavailability.
Patent Information
- Application Number
- CN202411272568.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing diclofenac sodium sustained-release tablets tend to be stratified in the gastrointestinal tract, the product quality is unstable, and the sustained-release parameters are uncontrollable, resulting in frequent gastrointestinal adverse reactions.
Modified colloidal silica and povidone K30 are used for one-time coating and sustained release, and secondary coating and sustained release are carried out through nano-silicon dioxide activation coating liquid to form high-density crosslinking points and organic-inorganic networks. Structure, enhance the coating effect.
It significantly reduces the stimulating effect of diclofenac sodium on the gastrointestinal mucosa, effectively reduces the incidence of gastrointestinal adverse reactions, and achieves a sustained release effect of at least 12 hours, improving the bioavailability of the drug.
Smart Images

Figure CN118806718B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sustained-release non-steroidal drugs, in particular to a diclofenac sodium sustained-release tablet and a preparation method thereof. Background Art
[0002] Diclofenac sodium is an organic compound, mainly used as an antipyretic analgesic, non-steroidal anti-inflammatory drug, and is commonly used in the treatment of various mild to moderate acute and chronic pain in orthopedics, such as osteoarthritis, rheumatoid arthritis, ankylosing spondylitis, etc. It mainly produces analgesic, anti-inflammatory and antipyretic effects by inhibiting cyclooxygenase and blocking the synthesis of prostaglandins. It is characterized by strong efficacy, mild adverse reactions, small dosage, small individual differences, and its effect is 2-2.5 times stronger than indomethacin and 26-50 times stronger than acetylsalicylic acid.
[0003] The plasma protein binding rate of diclofenac sodium is 99.7%, and the half-life is 1-2h. It is metabolized by the liver, and about 60% of the therapeutic dose of metabolites is excreted from the kidneys. The excretion of the original drug is less than 1%. The rest of the dose is excreted into the intestines through the bile in the form of metabolites and eliminated from the feces.
[0004] At present, although diclofenac sodium is a NSAIDs drug with high clinical safety, it still has gastrointestinal adverse reactions, such as upper abdominal discomfort, nausea, vomiting, etc. In severe cases, gastrointestinal bleeding may occur. Long-term use of diclofenac sodium may even increase the risk of gastrointestinal ulcer bleeding. Diclofenac sodium sustained-release tablets can achieve sustained release in the gastrointestinal tract and reduce the occurrence of adverse reactions. However, due to the large difference in particle size distribution between different materials and poor fluidity, there is a tendency to stratify during the descent process, the product quality is unstable, and the sustained-release parameters are uncontrollable, which needs to be solved urgently. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a diclofenac sodium sustained-release tablet and a preparation method thereof.
[0006] A diclofenac sodium sustained-release tablet comprises a core material and a coating layer wrapped on the surface of the core material.
[0007] The core material raw materials include, by mass: 80-120 parts of diclofenac sodium, 10-30 parts of colloidal silicon dioxide, 80-120 parts of sucrose, 18-36 parts of povidone K30, 31-63 parts of a blocker, and 1-3 parts of a lubricant.
[0008] The coating layer is obtained by spraying the coating liquid on the surface of the core material and then drying it; the raw materials of the coating liquid include, by mass: 1-3 parts of nano silicon dioxide, 0.01-0.1 parts of silane coupling agent, 4-10 parts of acrylic acid, 1-4 parts of butyl acrylate, 0.1-1 parts of initiator, 1-2 parts of plasticizer, 5-10 parts of anti-sticking agent, and 1-3 parts of calcium lactate.
[0009] Preferably, the retarder is cetyl alcohol and / or stearyl alcohol.
[0010] Preferably, the lubricant is magnesium stearate and / or calcium stearate.
[0011] Preferably, the silane coupling agent is propyltrimethoxysilane and / or 3-aminopropyltriethoxysilane.
[0012] Preferably, the initiator is ammonium persulfate.
[0013] Preferably, the plasticizer is triethyl citrate.
[0014] Preferably, the anti-sticking agent is talc.
[0015] Preferably, the colloidal silica is modified colloidal silica, and the modified colloidal silica is prepared by the following specific steps: adding sodium alginate to water, stirring at 80-90° C. for 10-20 min, adding sodium silicate thereto under stirring, stirring for 10-20 min, adding organic acid dropwise thereto under stirring, and stirring for 1-2 h.
[0016] Preferably, the mass ratio of sodium alginate to sodium silicate is 1-2:4-10.
[0017] Preferably, the organic acid is at least one of acetic acid, malic acid, tartaric acid and oxalic acid.
[0018] Preferably, the coating solution is prepared by the following specific steps: adding nano-silica to an ethanol aqueous solution and stirring evenly, adding a silane coupling agent, stirring at 50-80°C for 1-2 hours, filtering, washing, and vacuum drying to obtain activated silica; adding acrylic acid, butyl acrylate and activated silica to water and stirring evenly, adding an initiator, polymerizing at 80-90°C for 5-10 hours, cooling to room temperature, adjusting the pH value of the system to 5-6, and adding a plasticizer, an anti-sticking agent, and calcium lactate to mix evenly.
[0019] The above-mentioned method for preparing diclofenac sodium sustained-release tablets comprises the following steps:
[0020] S1. Put sucrose into a dust-free grinder with a sieve aperture of 1 mm, put it in a hopper mixer with povidone K30 and colloidal silicon dioxide, premix it at a speed of 5-10 r / min for 10-30 min, add diclofenac sodium and stir for 1-2 h at a stirring speed of 500-1000 r / min, and pass it through a swing granulator with a 40-mesh aperture to obtain a premix. a ;
[0021] S2, premix aAdd to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 60-80℃, and when the temperature reaches above 50℃, place the retarder in the hot melt granulator and stir for 10-30min, control the stirring speed to 100-180r / min, the chopping speed to 1000r / min, granulate, and when the material temperature reaches 50±1℃, discharge the material to obtain the premix b ;
[0022] S3, premix b While hot, pass through a swing granulator to granulate, the mesh number of the sieve is 10-20 mesh metal sieve, the granules are placed in a tray and cooled to 30-40℃, and then passed through a 10-20 mesh metal sieve to granulate, lubricant is added to it, and it is sent to a hopper mixer and mixed at a speed of 10-15r / min for 10-20min to obtain a premix c ;
[0023] S4, premix c Rotary tableting, tableting speed is 100,000-150,000 tablets / h, hardness is 5-12kg, tablet weight difference is ±5%, spray coating liquid on the surface of tablets after tableting to increase weight by 1.5-2.0%, and dry.
[0024] Beneficial effects: In the coating solution of the present invention, the nano-silicon dioxide is activated so that its surface contains a large number of amino groups and hydroxyl groups, which can disperse well with acrylic acid and butyl acrylate. Moreover, the coating solution obtained after the combination has high-density cross-linking points formed between molecules, and has good storage stability. At the same time, the highly dense organic-inorganic network structure of the coating solution has good stability for the premix. c The coating effect is excellent, and the particle size is smaller than that of silica, which can easily penetrate into the premix c surface, and through hydrogen bonding with the premix c Medium colloidal silicon dioxide has good affinity, further enhancing the coating effect.
[0025] In the modified colloidal silica of the present invention, sodium silicate and sodium alginate are compounded, organic acid promotes sodium silicate to generate silica sol, and then binds to sodium alginate, and the obtained modified colloidal silica is combined with polyvidone K30 to coat diclofenac sodium for a primary sustained release; then a coating solution is used for secondary coating and sustained release, and calcium lactate in the coating solution reacts with sodium alginate to form an outside-to-inside permeation cross-linking, which not only has excellent stability, but also allows diclofenac sodium to be slowly released after being taken, which can significantly reduce its irritation to the gastrointestinal mucosa, and effectively reduce the incidence of gastrointestinal adverse reactions of diclofenac sodium during the drug release process; after the coating layer is decomposed, it can ensure that diclofenac sodium is highly distributed in the gastrointestinal tract, and still does not produce irritation to the gastrointestinal tract, and can also achieve a sustained release effect of at least 12 hours, and the bioavailability of the drug is high.
[0026] The present invention not only avoids the burst release effect of traditional preparations and makes the sustained release parameters of the drug more controllable, but also can significantly increase the patient's compliance with medication and reduce the frequency of medication. The medication can be taken orally once a day, or after meals as prescribed by a doctor. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The graph is a graph showing the content changes of the diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 in a high temperature stability experiment.
[0028] Figure 2 The graph is a graph showing the content changes of the diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 in a high-humidity environment stability experiment.
[0029] Figure 3 The graph is a graph showing the content changes of the diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 in an accelerated stability test.
[0030] Figure 4 This is a comparison chart of the number of gastric mucosal ulcer points after oral administration of diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 to mice.
[0031] Figure 5 The cumulative release rate-time curve of the diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 during in vitro simulated digestion.
[0032] Figure 6 The graph is a blood drug concentration-time curve after the diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 were administered to Beagle dogs. DETAILED DESCRIPTION
[0033] The present invention will be further explained below in conjunction with specific embodiments.
[0034] Example 1: A diclofenac sodium sustained-release tablet, comprising: a core material and a coating layer wrapped on the surface of the core material. The core material raw materials include: 800g of diclofenac sodium, 100g of colloidal silicon dioxide, 800g of sucrose, 180g of povidone K30, 300g of hexadecanol, 10g of octadecyl alcohol, and 10g of magnesium stearate.
[0035] The above-mentioned method for preparing diclofenac sodium sustained-release tablets comprises the following steps:
[0036] S1. Put sucrose into a dust-free grinder with a sieve aperture of 1 mm, put it in a hopper mixer with povidone K30 and colloidal silicon dioxide, premix it at a speed of 5 r / min for 10 min, add diclofenac sodium and stir for 1 h at a stirring speed of 500 r / min, and pass it through a swing granulator with a 40-mesh aperture to obtain a premix. a ;
[0037] S2, premixa Add to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 60°C, wait until the temperature reaches above 50°C, place hexadecanol and octadecanol in the hot melt granulator and stir for 10 minutes, control the stirring speed to 100r / min, the chopping speed to 1000r / min, granulate, wait until the material temperature reaches 50±1°C, discharge the material to obtain the premix b ;
[0038] S3, premix b The granules were granulated by a swing granulator while hot, and the mesh size was 10 mesh metal sieve. The granules were placed in a tray and cooled to 30°C, and then granulated by a 10 mesh metal sieve. Magnesium stearate was added thereto, and the granules were sent to a hopper mixer and mixed at a speed of 10 r / min for 10 min to obtain a premix. c ;
[0039] S4, premix c The tablets were rotated to form tablets at a speed of 100,000 tablets / h, a hardness of 5 kg, and a tablet weight difference of ±5%. The coating liquid was sprayed on the surface of the tablets after tableting until the weight gain was 1.5%, and then dried.
[0040] The raw materials of the coating solution include: 100g of nano silicon dioxide, 1g of propyltrimethoxysilane, 400g of acrylic acid, 100g of butyl acrylate, 10g of ammonium persulfate, 100g of triethyl citrate, 500g of talc and 100g of calcium lactate.
[0041] The coating solution is prepared by the following specific steps: adding nano silicon dioxide to 2000g of 30% ethanol aqueous solution and stirring evenly, adding propyltrimethoxysilane, stirring at a temperature of 50°C for 1h, filtering, washing, and vacuum drying to obtain activated silicon dioxide; adding acrylic acid, butyl acrylate, and activated silicon dioxide to 3000g of water and stirring evenly, adding ammonium persulfate, polymerizing at a temperature of 80°C for 5h, cooling to room temperature, adjusting the pH value of the system to 5-6, adding triethyl citrate, talc, and calcium lactate, mixing evenly, and standing overnight.
[0042] Example 2: A diclofenac sodium sustained-release tablet, comprising: a core material and a coating layer wrapped on the surface of the core material. The core material raw materials include: 1200g of diclofenac sodium, 300g of colloidal silicon dioxide, 1200g of sucrose, 360g of povidone K30, 600g of hexadecanol, 30g of octadecyl alcohol, and 30g of magnesium stearate.
[0043] The above-mentioned method for preparing diclofenac sodium sustained-release tablets comprises the following steps:
[0044] S1. Put sucrose into a dust-free grinder and grind it. The mesh size of the grinder is 1mm. Put it into a hopper mixer with povidone K30 and colloidal silicon dioxide and premix it at a speed of 10r / min for 30min. Add diclofenac sodium and stir for 2h at a stirring speed of 1000r / min. Pass it through a swing granulator with a mesh size of 40 to obtain a premix. a ;
[0045] S2, premix a Add to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 80°C, wait until the temperature reaches above 50°C, place hexadecanol and octadecanol in the hot melt granulator and stir for 30 minutes, control the stirring speed to 180r / min, the chopping speed to 1000r / min, granulate, wait until the material temperature reaches 50±1°C, discharge the material to obtain the premix b ;
[0046] S3, premix b The granules were granulated by a swing granulator while hot, and the mesh size was 20 mesh metal sieve. The granules were placed in a tray and cooled to 40°C, and then granulated by a 20 mesh metal sieve. Magnesium stearate was added thereto, and the granules were sent to a hopper mixer and mixed at a speed of 15 r / min for 20 min to obtain a premix. c ;
[0047] S4, premix c The tablets were rotated to form tablets at a speed of 150,000 / h, a hardness of 12kg, and a tablet weight difference of ±5%. The coating liquid was sprayed on the surface of the tablets after tableting until the weight gain was 2.0%, and then dried.
[0048] The raw materials of the coating solution include: 300g of nano silicon dioxide, 10g of propyltrimethoxysilane, 1000g of acrylic acid, 400g of butyl acrylate, 100g of ammonium persulfate, 200g of triethyl citrate, 1000g of talc and 300g of calcium lactate.
[0049] The coating solution is prepared by the following specific steps: adding nano silicon dioxide to 4000g of 50% ethanol aqueous solution and stirring evenly, adding propyltrimethoxysilane, stirring at a temperature of 80°C for 2h, filtering, washing, and vacuum drying to obtain activated silicon dioxide; adding acrylic acid, butyl acrylate, and activated silicon dioxide to 6000g of water and stirring evenly, adding ammonium persulfate, polymerizing at a temperature of 90°C for 10h, cooling to room temperature, adjusting the pH value of the system to 5-6, adding triethyl citrate, talc, and calcium lactate, mixing evenly, and standing overnight.
[0050] Example 3: A diclofenac sodium sustained-release tablet, comprising: a core material and a coating layer wrapped on the surface of the core material. The core material raw materials include: 900g diclofenac sodium, 250g modified colloidal silicon dioxide, 900g sucrose, 320g povidone K30, 410g hexadecanol, and 25g magnesium stearate.
[0051] The modified colloidal silica was prepared by the following specific steps: 13 g of sodium alginate was added to 900 g of water, stirred at 82° C. for 18 min, 60 g of sodium silicate was added thereto under stirring, stirred for 18 min, 20 g of malic acid was added thereto dropwise under stirring, and stirred for 100 min.
[0052] The above-mentioned method for preparing diclofenac sodium sustained-release tablets comprises the following steps:
[0053] S1. Put sucrose into a dust-free grinder with a sieve aperture of 1 mm, put it in a hopper mixer with povidone K30 and modified colloidal silicon dioxide, premix it at a speed of 7 r / min for 25 min, add diclofenac sodium and stir for 80 min at a stirring speed of 900 r / min, and pass it through a swing granulator with a 40-mesh aperture to obtain a premix. a ;
[0054] S2, premix a Add to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 65°C, wait until the temperature reaches above 50°C, place hexadecanol in the hot melt granulator and stir for 25 minutes, control the stirring speed to 120r / min, the chopping speed to 1000r / min, granulate, wait until the material temperature reaches 50±1°C, discharge the material to obtain the premix b ;
[0055] S3, premix b The granules were granulated by a swing granulator while hot, and the mesh size was 18 mesh metal sieve. The granules were placed in a tray and cooled to 33°C, and then granulated by a 18 mesh metal sieve. Calcium stearate was added to the granules, and the granules were sent to a hopper mixer and mixed at a speed of 11 r / min for 17 minutes to obtain a premix. c ;
[0056] S4, premix c The tablets were rotated to form tablets at a speed of 110,000 / h, a hardness of 10kg, and a tablet weight difference of ±5%. The coating liquid was sprayed on the surface of the tablets after tableting until the weight gain was 1.6%, and then dried.
[0057] The raw materials of the coating solution include: 250g of nano silicon dioxide, 2g of 3-aminopropyltriethoxysilane, 800g of acrylic acid, 200g of butyl acrylate, 80g of ammonium persulfate, 130g of triethyl citrate, 900g of talc, and 150g of calcium lactate.
[0058] The coating solution is prepared by the following specific steps: adding nano silicon dioxide to 3500g of ethanol aqueous solution with a mass fraction of 35%, stirring evenly, adding 3-aminopropyltriethoxysilane, stirring at a temperature of 70°C for 80min, filtering, washing, and vacuum drying to obtain activated silicon dioxide; adding acrylic acid, butyl acrylate, and activated silicon dioxide to 5000g of water, stirring evenly, adding ammonium persulfate, polymerizing at a temperature of 82°C for 9h, cooling to room temperature, adjusting the pH value of the system to 5-6, adding triethyl citrate, talc, and calcium lactate, mixing evenly, and standing overnight.
[0059] Example 4: A diclofenac sodium sustained-release tablet, comprising: a core material and a coating layer wrapped on the surface of the core material. The core material raw materials include: 1100g of diclofenac sodium, 150g of modified colloidal silicon dioxide, 1100g of sucrose, 220g of povidone K30, 530g of hexadecanol, and 15g of magnesium stearate.
[0060] The modified colloidal silica was prepared by the following specific steps: 17 g of sodium alginate was added to 700 g of water, stirred at 88° C. for 12 min, 80 g of sodium silicate was added thereto under stirring, stirred for 12 min, 40 g of malic acid was added thereto dropwise under stirring, and stirred for 80 min.
[0061] The above-mentioned method for preparing diclofenac sodium sustained-release tablets comprises the following steps:
[0062] S1. Put sucrose into a dust-free grinder with a sieve aperture of 1 mm, put it in a hopper mixer with povidone K30 and modified colloidal silicon dioxide, premix it at a speed of 9 r / min for 15 min, add diclofenac sodium and stir for 100 min at a stirring speed of 700 r / min, and pass it through a swing granulator with a 40-mesh aperture to obtain a premix. a ;
[0063] S2, premix a Add to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 75°C, wait until the temperature reaches above 50°C, place hexadecanol in the hot melt granulator and stir for 15 minutes, control the stirring speed to 160r / min, the chopping speed to 1000r / min, granulate, wait until the material temperature reaches 50±1°C, discharge the material to obtain the premix b ;
[0064] S3, premix b The granules were granulated by a swing granulator while hot, and the mesh size was 12 mesh metal sieve. The granules were placed in a tray and cooled to 37°C, and then granulated by a 12 mesh metal sieve. Calcium stearate was added to the granules, and the granules were sent to a hopper mixer and mixed at a speed of 13 r / min for 13 minutes to obtain a premix. c ;
[0065] S4, premixc The tablets were rotated to form tablets at a speed of 130,000 / h, a hardness of 7kg, and a tablet weight difference of ±5%. The coating liquid was sprayed on the surface of the tablets after tableting until the weight gain was 1.9%, and then dried.
[0066] The raw materials of the coating solution include: 150g of nano silicon dioxide, 7g of 3-aminopropyltriethoxysilane, 600g of acrylic acid, 300g of butyl acrylate, 20g of ammonium persulfate, 170g of triethyl citrate, 700g of talc and 250g of calcium lactate.
[0067] The coating solution is prepared by the following specific steps: adding nano silicon dioxide to 2500g of 45% ethanol aqueous solution and stirring evenly, adding 3-aminopropyltriethoxysilane, stirring at a temperature of 60°C for 100min, filtering, washing, and vacuum drying to obtain activated silicon dioxide; adding acrylic acid, butyl acrylate, and activated silicon dioxide to 4000g of water and stirring evenly, adding ammonium persulfate, polymerizing at a temperature of 88°C for 7h, cooling to room temperature, adjusting the pH value of the system to 5-6, adding triethyl citrate, talc, and calcium lactate, mixing evenly, and standing overnight.
[0068] Example 5: A diclofenac sodium sustained-release tablet, comprising: a core material and a coating layer wrapped on the surface of the core material. The core material raw materials include: 1000g of diclofenac sodium, 200g of modified colloidal silicon dioxide, 1000g of sucrose, 270g of povidone K30, 450g of hexadecanol, 20g of octadecyl alcohol, and 20g of magnesium stearate.
[0069] The modified colloidal silica was prepared by the following specific steps: 15 g of sodium alginate was added to 800 g of water, stirred at 85° C. for 15 min, 70 g of sodium silicate was added thereto under stirring, stirred for 15 min, 30 g of acetic acid was added thereto dropwise under stirring, and stirred for 90 min.
[0070] The above-mentioned method for preparing diclofenac sodium sustained-release tablets comprises the following steps:
[0071] S1. Put sucrose into a dust-free grinder with a sieve aperture of 1 mm, put it in a hopper mixer with povidone K30 and modified colloidal silicon dioxide, premix it at a speed of 8 r / min for 20 min, add diclofenac sodium and stir for 90 min at a stirring speed of 800 r / min, and pass it through a swing granulator with a 40-mesh aperture to obtain a premix. a ;
[0072] S2, premix aAdd to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 70°C, wait until the temperature reaches above 50°C, place hexadecanol and octadecyl alcohol in the hot melt granulator and stir for 20 minutes, control the stirring speed to 140r / min, the chopping speed to 1000r / min, granulate, wait until the material temperature reaches 50±1°C, discharge the material to obtain the premix b ;
[0073] S3, premix b The granules were granulated by a swing granulator while hot, and the mesh size was 15 mesh metal sieve. The granules were placed in a tray and cooled to 35°C, and then granulated by a 15 mesh metal sieve. Magnesium stearate was added thereto, and the granules were sent to a hopper mixer and mixed at a speed of 12 r / min for 15 minutes to obtain a premix. c ;
[0074] S4, premix c The tablets were rotated to form tablets at a speed of 120,000 / h, a hardness of 8kg, and a tablet weight difference of ±5%. The coating liquid was sprayed on the surface of the tablets after tableting until the weight gain was 1.8%, and then dried.
[0075] The raw materials of the coating solution include: 200g of nano silicon dioxide, 5g of 3-aminopropyltriethoxysilane, 700g of acrylic acid, 250g of butyl acrylate, 50g of ammonium persulfate, 150g of triethyl citrate, 800g of talc and 200g of calcium lactate.
[0076] The coating solution is prepared by the following specific steps: adding nano silicon dioxide to 3000g of 40% ethanol aqueous solution and stirring evenly, adding 3-aminopropyltriethoxysilane, stirring at a temperature of 65°C for 90min, filtering, washing, and vacuum drying to obtain activated silicon dioxide; adding acrylic acid, butyl acrylate, and activated silicon dioxide to 4500g of water and stirring evenly, adding ammonium persulfate, polymerizing at a temperature of 85°C for 8h, cooling to room temperature, adjusting the pH value of the system to 5-6, adding triethyl citrate, talc, and calcium lactate, mixing evenly, and standing overnight.
[0077] Comparative Example 1: A diclofenac sodium sustained-release tablet, comprising: a core material and a coating layer wrapped on the surface of the core material. The core material raw materials include: 1000g of diclofenac sodium, 200g of modified colloidal silicon dioxide, 1000g of sucrose, 270g of povidone K30, 450g of hexadecanol, 20g of octadecyl alcohol, and 20g of magnesium stearate.
[0078] The modified colloidal silica was prepared by the following specific steps: 70 g of sodium silicate was added to 800 g of water, stirred at 85° C. for 15 min, 30 g of acetic acid was added dropwise thereto under stirring, and stirred for 90 min.
[0079] The above-mentioned method for preparing diclofenac sodium sustained-release tablets comprises the following steps:
[0080] S1. Put sucrose into a dust-free grinder with a sieve aperture of 1 mm, put it in a hopper mixer with povidone K30 and modified colloidal silicon dioxide, premix it at a speed of 8 r / min for 20 min, add diclofenac sodium and stir for 90 min at a stirring speed of 800 r / min, and pass it through a swing granulator with a 40-mesh aperture to obtain a premix. a ;
[0081] S2, premix a Add to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 70°C, wait until the temperature reaches above 50°C, place hexadecanol and octadecyl alcohol in the hot melt granulator and stir for 20 minutes, control the stirring speed to 140r / min, the chopping speed to 1000r / min, granulate, wait until the material temperature reaches 50±1°C, discharge the material to obtain the premix b ;
[0082] S3, premix b The granules were granulated by a swing granulator while hot, and the mesh size was 15 mesh metal sieve. The granules were placed in a tray and cooled to 35°C, and then granulated by a 15 mesh metal sieve. Magnesium stearate was added thereto, and the granules were sent to a hopper mixer and mixed at a speed of 12 r / min for 15 minutes to obtain a premix. c ;
[0083] S4, premix c The tablets were rotated to form tablets at a speed of 120,000 / h, a hardness of 8kg, and a tablet weight difference of ±5%. The coating liquid was sprayed on the surface of the tablets after tableting until the weight gain was 1.8%, and then dried.
[0084] The raw materials of the coating solution include: 200g of nano silicon dioxide, 5g of 3-aminopropyltriethoxysilane, 700g of acrylic acid, 250g of butyl acrylate, 50g of ammonium persulfate, 150g of triethyl citrate, 800g of talc and 200g of calcium lactate.
[0085] The coating solution is prepared by the following specific steps: adding nano silicon dioxide to 3000g of 40% ethanol aqueous solution and stirring evenly, adding 3-aminopropyltriethoxysilane, stirring at a temperature of 65°C for 90min, filtering, washing, and vacuum drying to obtain activated silicon dioxide; adding acrylic acid, butyl acrylate, and activated silicon dioxide to 4500g of water and stirring evenly, adding ammonium persulfate, polymerizing at a temperature of 85°C for 8h, cooling to room temperature, adjusting the pH value of the system to 5-6, adding triethyl citrate, talc, and calcium lactate, mixing evenly, and standing overnight.
[0086] Comparative Example 2: A diclofenac sodium sustained-release tablet, comprising: a core material and a coating layer wrapped on the surface of the core material. The core material raw materials include: 1000g of diclofenac sodium, 200g of modified colloidal silicon dioxide, 1000g of sucrose, 270g of povidone K30, 450g of hexadecanol, 20g of octadecyl alcohol, and 20g of magnesium stearate.
[0087] The modified colloidal silica was prepared by the following specific steps: 15 g of sodium alginate was added to 800 g of water, stirred at 85° C. for 15 min, 70 g of sodium silicate was added thereto under stirring, stirred for 15 min, 30 g of acetic acid was added thereto dropwise under stirring, and stirred for 90 min.
[0088] The above-mentioned method for preparing diclofenac sodium sustained-release tablets comprises the following steps:
[0089] S1. Put sucrose into a dust-free grinder with a sieve aperture of 1 mm, put it in a hopper mixer with povidone K30 and modified colloidal silicon dioxide, premix it at a speed of 8 r / min for 20 min, add diclofenac sodium and stir for 90 min at a stirring speed of 800 r / min, and pass it through a swing granulator with a 40-mesh aperture to obtain a premix. a ;
[0090] S2, premix a Add to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 70°C, wait until the temperature reaches above 50°C, place hexadecanol and octadecyl alcohol in the hot melt granulator and stir for 20 minutes, control the stirring speed to 140r / min, the chopping speed to 1000r / min, granulate, wait until the material temperature reaches 50±1°C, discharge the material to obtain the premix b ;
[0091] S3, premix b The granules were granulated by a swing granulator while hot, and the mesh size was 15 mesh metal sieve. The granules were placed in a tray and cooled to 35°C, and then granulated by a 15 mesh metal sieve. Magnesium stearate was added thereto, and the granules were sent to a hopper mixer and mixed at a speed of 12 r / min for 15 minutes to obtain a premix. c ;
[0092] S4, premix c The tablets were rotated to form tablets at a speed of 120,000 / h, a hardness of 8kg, and a tablet weight difference of ±5%. The coating liquid was sprayed on the surface of the tablets after tableting until the weight gain was 1.8%, and then dried.
[0093] The raw materials of the coating solution include: 200g of nano silicon dioxide, 700g of acrylic acid, 250g of butyl acrylate, 50g of ammonium persulfate, 150g of triethyl citrate, 800g of talc and 200g of calcium lactate.
[0094] The coating solution is prepared by the following specific steps: adding acrylic acid, butyl acrylate and nano-silicon dioxide to 4500g of water and stirring evenly, adding ammonium persulfate, polymerizing at a temperature of 85°C for 8h, cooling to room temperature, adjusting the pH value of the system to 5-6, adding triethyl citrate, talc and calcium lactate, mixing evenly, and standing overnight.
[0095] 1. The stability test of the diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 was performed as follows:
[0096] (1) The diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 were placed in a constant temperature box at 60±2°C for 10 days, and samples were taken and observed at 0, 5, and 10 days respectively.
[0097] Each group of diclofenac sodium sustained-release tablets is always white and has a smooth surface, and the content is Figure 1 As shown, the high temperature stability of the diclofenac sodium sustained-release tablets obtained in Example 5 is better than that in Comparative Examples 1-2.
[0098] (2) The diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 were placed in an environment at 25° C. and the relative humidity was adjusted to 75±5% RH for 10 days. Samples were taken and observed at 0, 5, and 10 days respectively.
[0099] Each group of diclofenac sodium sustained-release tablets is always white and has a smooth surface, and the content is Figure 2 As shown, the high humidity environment stability of the diclofenac sodium sustained-release tablets obtained in Example 5 is better than that of Comparative Examples 1-2.
[0100] (3) The diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 were placed in a constant temperature and humidity chamber at a temperature of 40±2°C and a relative humidity of 75±5%RH for 6 months. Samples were taken and observed at the 0th, 1st, 2nd, 4th and 6th month respectively.
[0101] Each group of diclofenac sodium sustained-release tablets is always white and has a smooth surface, and the content is Figure 3 As shown, the accelerated test stability of the diclofenac sodium sustained-release tablets obtained in Example 5 is better than that in Comparative Examples 1-2.
[0102] 2. The gastric irritation test was carried out using the diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2, as follows:
[0103] Kunming mice were used as test animals. Healthy mice weighing 20.5±1.7g were selected and randomly divided into 4 groups. They were fasted for 24h before the experiment and had free access to water. Diclofenac sodium original drug and diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 were gavaged at 180mg / kg of body weight. They were killed 6h later, and the stomach was immediately dissected and fixed in formaldehyde solution for 5min, then cut open along the greater curvature of the stomach and the stomach contents were washed, and the gastric mucosal damage was observed under a dissecting microscope. The total number of ulcer points in each animal was counted.
[0104] like Figure 4 As shown, the total number of ulcer points of mice in Example 5 and Comparative Examples 1-2 was less than that in the diclofenac sodium original drug group (P < 0.05), indicating that the encapsulated sustained-release treatment of diclofenac sodium can effectively reduce its irritation to the gastric mucosa; and the total number of ulcer points of mice in Example 5 was the least, which was better than that in Comparative Examples 1-2 (P < 0.05).
[0105] 3. The diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 were subjected to in vitro simulated digestion treatment, as follows:
[0106] Each group of diclofenac sodium sustained-release tablets was placed in artificial gastric juice for 4 hours, and samples were taken at 0, 2, and 4 hours and fresh artificial gastric juice was added. The diclofenac sodium content in the solution was detected; then the remaining diclofenac sodium sustained-release tablets were filtered out and placed in artificial intestinal juice for 8 hours. Samples were taken at 6, 8, 10, and 12 hours of total digestion (i.e., 2, 4, 6, and 8 hours in artificial intestinal juice) and fresh artificial intestinal juice was added. The diclofenac sodium content in the solution was detected. The cumulative release rate of diclofenac sodium was calculated and plotted.
[0107] like Figure 5 As shown, each group of diclofenac sodium sustained-release tablets is almost insoluble in artificial gastric juice, which can effectively avoid diclofenac sodium irritation to gastric mucosa, which is consistent with the above results; after entering the artificial intestinal juice, each group of diclofenac sodium sustained-release tablets began to disintegrate, and the diclofenac sodium sustained-release tablets obtained in Example 5 had the best sustained-release effect, and the cumulative release rate of diclofenac sodium after a total digestion of 12 hours was 81.67%.
[0108] 4. The diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2 were used to test the blood drug concentration at different times after taking the tablets, as follows:
[0109] Beagle dogs were used as test animals. Healthy Beagle dogs weighing 12.93±0.31 kg at 12 months old were selected and randomly divided into 3 groups. They were fasted for 12 hours before the experiment and had free access to water. Each group of Beagle dogs was gavaged with the diclofenac sodium sustained-release tablets obtained in Example 5 and Comparative Examples 1-2, respectively, and the dose of each group was 100 mg of diclofenac sodium.
[0110] Before administration and 0.5, 1, 2, 3, 4, 6, 8, 12 and 24 h after administration, 3 mL of blood was collected from the forelimb vein, placed in a heparinized test tube, and immediately centrifuged at 4°C for 10 min (28621×g). 50 μL of the upper plasma was placed in a 1.5 mL EP tube, 400 μL of the internal standard solution was added, mixed and centrifuged for 10 min (15200×g), and 5 mL of the supernatant was injected for UPLC-MS / MS quantitative analysis.
[0111] Internal standard solution: Accurately weigh 1.88 mg of rhein standard, add 200 mL DMSO to dissolve and dilute with 740 mL acetonitrile, shake well to prepare a rhein stock solution with a mass concentration of 2000 mg / mL. Take an appropriate amount of the rhein stock solution and dilute it with acetonitrile containing 0.1% formic acid to a concentration of 10.0 ng / mL.
[0112] Chromatographic conditions: Column: BEH C 18 (2.1 mm × 100 mm, 1.7 mm, Waters); mobile phase: acetonitrile-2 mmol / L ammonium acetate-formic acid (70:30:0.1, v / v / v); flow rate: 0.3 mL / min -1 ; Analysis time: 2min; Column temperature: 25℃; Autosampler temperature: 4℃; Injection volume: 5mL.
[0113] Mass spectrometry conditions: ion source: electrospray ion source (ESI), negative ion detection; ion source voltage (IS): -4500V; ion source temperature (TEM): 500℃; nebulizer gas (Gas1, N2) pressure: 345kPa; auxiliary gas (Gas2, N2) pressure: 345kPa; curtain gas (CUR) pressure: 138kPa; scanning mode: multiple reaction monitoring (MRM); collision gas (CAD, N2) pressure: Medium; the ion reactions used for quantitative analysis are: m / z (293.9+293.9+296.1)→(249.9+213.7+251.8) (DS, DP voltage: -47V, -47V, -53V, CE voltage: -18V, -30V, -15V; CXP voltage: -13V, -15V, -15V), and m / z 283.0→239.0 (rhein, DP voltage: -80 V, CE voltage: -22 V; CXP voltage: -17 V).
[0114] like Figure 6As shown, the maximum blood drug concentration of Example 5 group is not as high as that of Comparative Examples 1-2 groups, but the blood drug concentration of Example 5 group always rises and falls slowly, which not only avoids the burst release effect of traditional preparations, effectively reduces the incidence of gastrointestinal adverse reactions of diclofenac sodium during the drug release process, but also maintains the blood drug concentration in a suitable range, achieves a sustained release effect, improves the bioavailability of the drug, and can significantly increase the patient's compliance with the drug and reduce the frequency of drug administration.
[0115] The reason for the above results is that: in the coating solution of the present invention, the nano-silicon dioxide is activated so that its surface contains a large number of amino groups and hydroxyl groups, which can disperse well with acrylic acid and butyl acrylate. Moreover, the coating solution obtained after the combination has high-density cross-linking points formed between molecules, and has good storage stability. At the same time, the highly dense organic-inorganic network structure of the coating solution has good stability for the premix. c The coating effect is excellent, and the particle size is smaller than that of silica, which can easily penetrate into the premix c surface, and through hydrogen bonding with the premix c The modified colloidal silica has good affinity, which further enhances the coating effect. In the modified colloidal silica of the present invention, sodium silicate and sodium alginate are compounded, and organic acid promotes sodium silicate to generate silica sol, and binds to sodium alginate. The obtained modified colloidal silica is combined with polyvidone K30 to coat diclofenac sodium for sustained release once; then a coating solution is used for secondary coating and sustained release, and calcium lactate in the coating solution reacts with sodium alginate to form an external to internal permeable crosslinking, which not only has excellent stability, but also allows diclofenac sodium to be slowly released after being taken, which can significantly reduce its irritation to the gastrointestinal mucosa, and effectively reduce the incidence of gastrointestinal adverse reactions of diclofenac sodium during the drug release process. After the coating layer is decomposed, it can ensure that diclofenac sodium is highly distributed in the gastrointestinal tract, and still will not produce irritation to the gastrointestinal tract, and can also achieve a sustained release effect of at least 12 hours, and the bioavailability of the drug is high.
[0116] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A diclofenac sodium sustained-release tablet, characterized in that: include: A core material and a coating layer wrapped on the surface of the core material; The core material raw materials include, by mass: 80-120 parts of diclofenac sodium, 10-30 parts of colloidal silicon dioxide, 80-120 parts of sucrose, 18-36 parts of povidone K30, 31-63 parts of a blocker, and 1-3 parts of a lubricant; The colloidal silica is modified colloidal silica, and the modified colloidal silica is prepared by the following specific steps: adding sodium alginate to water, stirring at 80-90° C. for 10-20 minutes, adding sodium silicate thereto under stirring, stirring for 10-20 minutes, adding organic acid thereto dropwise under stirring, and stirring for 1-2 hours; The coating layer is obtained by spraying the coating liquid on the surface of the core material and then drying it; the raw materials of the coating liquid include, by weight: 1-3 parts of nano silicon dioxide, 0.01-0.1 parts of silane coupling agent, 4-10 parts of acrylic acid, 1-4 parts of butyl acrylate, 0.1-1 parts of initiator, 1-2 parts of plasticizer, 5-10 parts of anti-sticking agent, and 1-3 parts of calcium lactate; The silane coupling agent is 3-aminopropyltriethoxysilane; The coating solution is prepared by the following specific steps: adding nano silicon dioxide to an ethanol aqueous solution and stirring evenly, adding a silane coupling agent, stirring at 50-80°C for 1-2 hours, filtering, washing, and vacuum drying to obtain activated silicon dioxide; adding acrylic acid, butyl acrylate and activated silicon dioxide to water and stirring evenly, adding an initiator, polymerizing at 80-90°C for 5-10 hours, cooling to room temperature, adjusting the pH value of the system to 5-6, and adding a plasticizer, an anti-sticking agent, and calcium lactate and mixing evenly.
2. The diclofenac sodium sustained-release tablet according to claim 1, characterized in that: The retardant is cetyl alcohol and / or octadecyl alcohol.
3. The diclofenac sodium sustained-release tablet according to claim 1, characterized in that: The lubricant is magnesium stearate and / or calcium stearate.
4. The diclofenac sodium sustained-release tablet according to claim 1, characterized in that: The initiator is ammonium persulfate.
5. The diclofenac sodium sustained-release tablet according to claim 1, characterized in that: The plasticizer is triethyl citrate and the anti-adhesive agent is talc.
6. The diclofenac sodium sustained-release tablet according to claim 1, characterized in that: The mass ratio of sodium alginate to sodium silicate is 1-2:4-10.
7. A method for preparing the diclofenac sodium sustained-release tablets according to any one of claims 1 to 6, characterized in that: The steps include: S1. Crush sucrose and premix with povidone K30 and colloidal silicon dioxide for 10-30 min, add diclofenac sodium and stir for 1-2 h to obtain a premix. a ; S2, premix a Add to the hot melt granulator, set the water inlet temperature of the hot melt granulator to 60-80℃, wait until the temperature reaches above 50℃, place the retarder in the hot melt granulator and stir for 10-30min, granulate, wait until the material temperature reaches 50±1℃, discharge the material to obtain the premix b ; S3, premix b The granules are granulated while hot, cooled to 30-40°C, and lubricants are added thereto and mixed for 10-20 minutes to obtain a premix. c ; S4, premix c The tablets are rotated and the coating liquid is sprayed on the surface of the tablets after tableting to a weight gain of 1.5-2.0%, and then dried.
Citation Information
Patent Citations
Arsenic-trioxide-carrying pH-responsive mesoporous silica nanoparticle and preparation method thereof
CN104644573A
Diclofenac sodium sustained-release tablets and preparation method thereof
CN107951856A